Community Currencies as Crisis Response: Results From a Randomized Control Trial in Kenya - Mqamelo, Rebecca (Frontiers in Blockchain, 2022)
This paper presents the results of what may be the world’s first randomized control trial on community currencies, focusing on Grassroots Economics' Community Inclusion Currency (CIC) model run on the xDAI blockchain. Beneficiaries in Nairobi, Kenya were sent the equivalent of $30 in cryptocurrency tokens, enabling a level of impact evaluation usually unfeasible for most cash and mobile-money based transfer programs. Results show that CIC transfers of $30 are associated with a $93.51 increase in beneficiaries' wallet balance, a $23.17 increase in monthly income, a $16.30 increase in monthly spending, a $6.31 increase in average trade size and a $28.43 increase in expenditure on food and water. However, the difference in treatment effects for males versus females suggests gender imbalances persist. This study serves as an important prototype for novel cash transfer models and presents some of the first quantitative evidence in the area of “crypto for good”.